Mitochondrial mutations in protein coding genes of respiratory chain including complexes IV, V, and MT-TRNA genes are associated risk factors for congenital heart disease - Heidari, Mohammad Mehdi (2022)
Most studies aiming at unraveling the molecular events associated with cardiac congenital heart disease (CHD) have focused on the effect of mutations occurring in the nuclear genome. In recent years, a significant role has been attributed to mitochondria for correct heart development and maturation of cardiomyocytes. Moreover, numerous heart defects have been associated with nucleotide variations occurring in the mitochondrial genome, affecting mitochondrial functions and cardiac energy metabolism, including genes encoding for subunits of res-piratory chain complexes. Therefore, mutations in the mitochondrial genome may be a major cause of heart dis-ease, including CHD, and their identification and characterization can shed light on pathological mechanisms occurring during heart development. Here, we have analyzed mitochondrial genetic variants in previously re-ported mutational genome hotspots and the flanking regions of mt-ND1, mt-ND2, mt-COXI, mt-COXII, mt-ATPase8, mt-ATPase6, mt-COXIII, and mt-tRNAs (Ile, Gln, Met, Trp, Ala, Asn, Cys, Tyr, Ser, Asp, and Lys) en-coding genes by polymerase chain reaction-single stranded conformation polymorphism (PCR-SSCP) in 200 pa-tients with CHD, undergoing cardiac surgery. A total of 23 mitochondrial variations (5 missense mutations, 8 synonymous variations, and 10 nucleotide changes in tRNA encoding genes) were identified and included 16 novel variants. Additionally, we showed that intracellular ATP was significantly reduced (P=0.002) in CHD pa-tients compared with healthy controls, suggesting that the mutations have an impact on mitochondrial energy production. Functional and structural alterations caused by the mitochondrial nucleotide variations in the gene products were studied in-silico and predicted to convey a predisposing risk factor for CHD. Further studies are necessary to better understand the mechanisms by which the alterations identified in the present study contribute to the development of CHD in patients.